2016
DOI: 10.18632/oncotarget.9516
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of hemoglobin to red cell distribution width as a novel prognostic parameter in esophageal squamous cell carcinoma: a retrospective study from southern China

Abstract: BackgroundWe propose a novel prognostic parameter for esophageal squamous cell carcinoma (ESCC)—hemoglobin/red cell distribution width (HB/RDW) ratio. Its clinical prognostic value and relationship with other clinicopathological characteristics were investigated in ESCC patients.ResultsThe optimal cut-off value was 0.989 for the HB/RDW ratio. The HB/RDW ratio (P= 0.035), tumor depth (P = 0.020) and lymph node status (P<0.001) were identified to be an independent prognostic factors of OS by multivariate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
113
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(127 citation statements)
references
References 45 publications
7
113
1
6
Order By: Relevance
“…However, Zhang et al reported that RDW was no longer associated with either OS or DFS after adjustment for age, lymph node metastasis, TNM stage, adjuvant therapy, smoking status, maximum tumor diameter, MPV, PLT, CA19-9, NLR (Neutrophil-lymphocyte ratio) and COP-MPV (combination of platelet count and MPV). Notably, in the study of Sun (34), while the crude RDW showed no significant association with OS the combination of RDW and HB values in the form of hemoglobin/red blood cell distribution width (HB/RDW) ratio was found independently associated with OS even after adjusting for lymph node status, tumor depth, treatment, tumor size and the Glasgow prognostic score (GPS). Interesting, Hirahara and colleagues (36) found that a high RDW is potentially an independent risk factor for a worse prognosis in non-elderly patients, but not in elderly patients.…”
Section: Role Of Rdw In Solid Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Zhang et al reported that RDW was no longer associated with either OS or DFS after adjustment for age, lymph node metastasis, TNM stage, adjuvant therapy, smoking status, maximum tumor diameter, MPV, PLT, CA19-9, NLR (Neutrophil-lymphocyte ratio) and COP-MPV (combination of platelet count and MPV). Notably, in the study of Sun (34), while the crude RDW showed no significant association with OS the combination of RDW and HB values in the form of hemoglobin/red blood cell distribution width (HB/RDW) ratio was found independently associated with OS even after adjusting for lymph node status, tumor depth, treatment, tumor size and the Glasgow prognostic score (GPS). Interesting, Hirahara and colleagues (36) found that a high RDW is potentially an independent risk factor for a worse prognosis in non-elderly patients, but not in elderly patients.…”
Section: Role Of Rdw In Solid Cancersmentioning
confidence: 99%
“…To date, five studies have investigated the prognostic value of RDW in esophageal cancer (34)(35)(36)(37)(38). The study characteristics and the main findings of these studies are reported in Table 2.…”
Section: Role Of Rdw In Solid Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al[8] proposed to calculate the ratio of hemoglobin (Hb) to RDW ( i.e ., Hb/RDW) as a novel prognostic factor in patients with ESCC. They observed that patients with a Hb/RDW ratio of < 0.989 had a 1.4-time higher risk of death during follow up compared to patients with Hb/RDW ratio > 0.989 (95%CI: 1.024-1.958, P = 0.035)[8].…”
Section: Role Of Rdw In Gut Disordersmentioning
confidence: 99%
“…Based on research related to Hb and RDW in malignant tumors, Sun et al . was the first to report the prognostic value of the baseline Hb‐to‐RDW ratio (HRR) in esophageal squamous cell carcinoma (ESCC) in 2016.…”
Section: Introductionmentioning
confidence: 99%